Do Direct Elections Matter? Quasi-experimental Evidence from Germany - Stefanie Gäbler; Felix Rösel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
We estimate the causal effect of direct elections on the economic performance of politicians. Candidates running in direct elections to head local governments in the German state of Brandenburg need an absolute majority, and votes for the winner must represent at least 15% of eligible voters. If the quorum is not reached, direct elections are suspended, and local councils appoint the head of government. We examine election outcomes around the quorum, where the form of government is arguably exogenous. Event study results show that the public employment service becomes somewhat more effective under directly elected politicians. However, directly elected politicians do not seem to attract more businesses or expedite administrative acts.
Keywords: D72; H40; H75; R50; 330; Direct elections; constitutions; government form; local government; economic; performance; public services; Germany